PENGARUH WAKTU DAN NUTRIEN PADA PROSES FERMENTASI SAMPAH ORGANIK MENJADI BIOETANOL DENGAN METODE SSF - Adha Ilmi Nuraini; Naniek Ratni J.A.R (EnviroUS, 2021)
Bioethanol is a renewable and environmentally friendly energy source that can overcome the depletion of oil resources in Indonesia and reduce the increase in greenhouse gases. Organic waste can be one of the raw materials for bioethanol production because of its abundant availability. This research was conducted to determine the potential for organic waste to be processed into bioethanol. This study used vegetable waste, fruit waste, and leaf waste and then fermented using yeast containing Saccharomyces c. The addition of nutrients (urea and NPK) and fermentation time for 3 days, 5 days, and 7 days were carried out to determine the effect on the resulting ethanol content. The production of bioethanol is carried out using the SSF (Simultaneous Saccharification and Fermentation) method so that the hydrolysis and fermentation processes occur simultaneously. The results showed that the highest ethanol content was 18.79% with a fermentation time of 5 days and the addition of 25 gr urea. The addition of nutrients and fermentation time affects the ethanol levels produced.